Metanephrine and normetanephrine associated with subclinical myocardial injuries in pheochromocytoma and paraganglioma - Yu, Yang; Chen, Chuyun; Han, Wencong; Zhang, Yan; Zhang, Zheng; Yang, Ying (Frontiers in Oncology, 2022)
Objective To analyze the correlation between metanephrine and normetanephrines (MNs) and subclinical myocardial injuries (SMI) diagnosed by low left ventricular global longitudinal strain (LV GLS) in patients with pheochromocytoma and paraganglioma (PPGL). Methods Seventy-six patients who underwent surgery for pheochromocytoma or paraganglioma from September 2017 to April 2022 were examined. All the patients enrolled had normal left ventricular ejection fraction (LVEF) and myocardial injury biomarkers including cardiac troponin I and B-natriuretic peptide. Univariate analysis and multivariate analysis were performed to evaluate the association of MNs and subclinical myocardial injury (SMI)(defined as LV GLS<18). Results LV GLS of 13(17.11%) PPGL patients was less than 18. The percentage of patients with elevation of single hormone (metanephrine, normetanephrine, 3-methoxytyramine) or any one of MNs was not significantly correlated with SMI (P=0.987, 0.666, 0.128 and 0.918, respectively). All MNs elevation was associated with SMI (OR: 11.27; 95% CI, 0.94—135.24; P= 0.056). After adjusting for age, All MNs elevation was significantly correlated with SMI (OR: 16.54; 95% CI, 1.22—223.62; P= 0.035). Conclusion MNs might be an important factor influencing myocardial function. All MNs elevation might indicate SMI. If all MNs elevated, LV GLS measurement was recommended for PPGL patients to detect SMI in the absence of decrease LVEF or other heart disease in clinical practice.